Relative density and distribution of tantalus monkey (Cercopithecus tantalus) in the four ranges of Sambisa game reserve (2015)
Tantalus monkey (Cercopithecus tantalus) was reported as widely abundant primate species in Sambisa Game Reserve. In order to provide information on the density of Tantalus monkey, this research was undertaken to study the abundance and distribution of the species in the Reserve. The line transects method of estimating animal population was used for the enumeration. An analysis of data was conducted using the software package DISTANCE 6.0 to determine population density estimate. Kwada, Yuwe, Jeltere and Balda are the four ranges within the reserve. Considering the number of species sighted, Tantalus monkey is widespread throughout the reserve where it was sighted in all the 4 ranges with the highest density of 10.84 km-2 (n=80) in Yuwe range. In Jeltere ecological habitat for the species survival is under threats. Habitat loss and habitat degradation in the area are principally due to illegal logging, forest fires and forest clearance for agriculture harbored very few individual of the species. The mean encounter rates (MERs) for the species 1.58km-1 with density estimate of about 11km-2. There was a significant difference in the pattern of the species densities for morning and evening count indicating less activity in the evening with mean encounter rate of 0.54 km-1 (n=85) and 0.43 km-1 (n= 67) individual animals for morning and evening sightings respectively. The relative density for the species across the four ranges in the reserve revealed that Tantalus monkey was present in all the four ranges of the game reserve. A total of only 21 Tantalus monkey were sighted in the Balda range, this calls for close monitoring and control of its population particularly within the range.